2009
DOI: 10.1152/ajpcell.00060.2009
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated maturation of Ca2+ handling properties of human embryonic stem cell-derived cardiomyocytes by calsequestrin expression

Abstract: RA. Facilitated maturation of Ca 2ϩ handling properties of human embryonic stem cell-derived cardiomyocytes by calsequestrin expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 40 publications
8
89
0
Order By: Relevance
“…The small overlap maybe attributed to the precipitation of plasma membrane proteins during 2D-differential-in-gel electrophoresis experiments and are, therefore, mostly excluded from our analysis 43 Gundry et al 44 examined published proteomic data on pluripotent stem cells and showed that overlap among different proteomic studies are generally small and this is consistent with what we observed. Of the ones that were found in both the studies, only 31% showed concordant changes between -handling proteins, 45 microRNAs, 46 and epigenetic components 47 that are determinants of the maturation of hESC-CMs. Led by these data and other clues, we found that induced contractions via electric stimulation increase the expression of contractile genes and improve the organization of myofilaments.…”
Section: Discussionmentioning
confidence: 93%
“…The small overlap maybe attributed to the precipitation of plasma membrane proteins during 2D-differential-in-gel electrophoresis experiments and are, therefore, mostly excluded from our analysis 43 Gundry et al 44 examined published proteomic data on pluripotent stem cells and showed that overlap among different proteomic studies are generally small and this is consistent with what we observed. Of the ones that were found in both the studies, only 31% showed concordant changes between -handling proteins, 45 microRNAs, 46 and epigenetic components 47 that are determinants of the maturation of hESC-CMs. Led by these data and other clues, we found that induced contractions via electric stimulation increase the expression of contractile genes and improve the organization of myofilaments.…”
Section: Discussionmentioning
confidence: 93%
“…These maturity genes include CASQ2, whose forced overexpression in fetal-like hiPSC-derived cardiomyocytes results in a more mature calcium handling phenotype [35]. Beyond CASQ2, CRYAB and DESMIN (not shown) were identified as maturation genes.…”
Section: Babiarz Et Almentioning
confidence: 99%
“…Following blasticidin selection, cultures were maintained in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum for the duration of the cultures. On days 0, 3,7,10,14,20,28,35,45,60,90, and 120, approximately 3 million cells were removed for RNA collection. The differentiation protocol and sample collection were performed in 3 independent replicates as indicated by Run 1, 2, and 3 in Figs.…”
Section: Cardiomyocyte Differentiationmentioning
confidence: 99%
“…A similar trend was also observed in cultured embryonic stem cells. 31,32 However, while embryonic stem cell cultures can be used successfully to investigate prenatal heart development, 33,34 the formation of contracting cardiomyocyte colonies is more relevant to postnatal cardiomyogenesis.…”
Section: Cardiomyogenic Differentiation Of Isl1mentioning
confidence: 99%